Skills Development in the Informal Sector of Sub-Saharan Africa - Adams, Arvil V. (World Bank, Washington, DC, 2017)
Since first recognized in the early 1970s, the informal sector of Sub?Saharan Africa has become a growing source of employment for large numbers of youths, but also older workers pursuing entrepreneurial goals and others adjusting to structural changes in the region's employment. Initially viewed as a safety net for those unable to find employment in the modern sector, the image of the informal sector has begun to change with time and the education of those entering it. More workers have begun to view it, not as a temporary stop while searching for employment in the formal wage economy, but as a preferred destination offering opportunities to those wanting to become entrepreneurs. The chapter examines recent research covering measurement of employment in the informal sector, impediments to investing in skills within the sector, and policies and programs to expand this investment. It extends earlier work on this topic done under auspices of the World Bank. The purpose is to examine what is currently known about these issues, identify gaps in knowledge, and offer a strategy for expanding skills development in the informal sector. Recent research, for example, like that mentioned above in Ghana showing the changing character of employment in the informal sector and the prospect of growing returns to skills casts a new light on employment in this sector and merits further inquiry into the robustness of these findings in other countries to deepen our understanding of how skills influence the welfare of those who create their own employment in the informal sector and how the investment in skills can be expanded.